SILORANE INCORPORATED WITH HYDROXYAPATITE AND FLUOROAPATITE -TO INVENT A NEW BIOACTIVE RESTORATIVE MATERIAL - Shoaib Khan; Madiha Pirvani; Saad Bin Irfan; Saima Akram; Mariam Qidwai; Mohammad Asif Nathani (ziauddin University, 2024)
Background: There were a number of restorative materials, which were fulfilling the requirements of a dental restorative material partially or somewhat completely with some limitations. 3M ESPE recently introduced a new dental restorative material, Filtek™ Silorane, which was claimed to fulfil the main objective completely, which was even confirmed by the recent studies. In order to make the best available dental restorative material an ideal restorative material it has to be bioactive. This study has been planned for the invention of a Silorane based bioactive material. It was proposed to incorporate the known bioactive materials (Hydroxyapatite and Fluoroapatite) in Silorane and analyze its chemical characterization. The main objective of a restorative dental material is to restore the function and aesthetics of the dental patient. Methods: Hydroxyapatite and Fluoroapatite were synthesized and incorporated in Silorane by 5, 10, 40, 50 and 60% weight ratio. The resultant samples were chemically analyzed by FTIR and Raman Spectroscopy. Results: The incorporation of synthesized Hydroxyapatite and Fluoroapatite into Silorane resulted in the innovation of a new bioactive restorative material. The resultant FTIR and Raman spectra shows that the Silorane incorporated by 40, 50 and 60% hydroxyapatite and fluoroapatite were altering the chemical structure of Silorane while spectrum of the samples with 5 and 10% of hydroxyapatite and fluoroapatite shows the apatites presence without changing the chemical structure of Silorane. Conclusion: A novel bioactive restorative material was invented by the incorporation of synthesized nano-Hydroxyapatite and Fluoroapatite into Filtek™ Silorane. The chemical characterization showed that bond was formed between the apatites and siloxane functional groups which results in the best available dental restorative material.